Intraperitoneal Granulomas Unexpectedly Found during a Cesarean Delivery: A Late Complication of Dropped Gallstones - David A. Suarez-Zamora; Luis E. Barrera-Herrera; Ricardo Caceres-Mileo; Mauricio A. Palau-Lazaro (Case Reports in Pathology)
Laparoscopic cholecystectomy is the treatment of choice for patients with symptomatic cholelithiasis. Spillage of gallstones into the abdominal cavity during laparoscopic cholecystectomy occurs in approximately one-third of cases. Although retained gallstones remain asymptomatic, few cases may develop complications. We report the case of a 29-year-old nulliparous woman presenting with several hard nodules in the omentum, raising the possibility of a metastatic disease. Histological examination demonstrated a bile-stained material and a foreign body-type granulomatous response without neoplastic tissue. Our case demonstrates an example of a complication resulting two years after a laparoscopic cholecystectomy that was unexpectedly found during a cesarean delivery. Pathologists should be aware of this entity to avoid interpretation errors.